Versatile roles of ubiquitous calcium-dependent protein kinases (CDPKs) in plants: VERSATILE ROLES OF UBIQUITOUS CALCIUM-DEPENDENT PROTEIN KINASES (CDPKs) IN PLANTS - SUJATHA THANKESWARAN PARVATHY (Journal of Oilseeds Research, 2018)
Calcium-dependent protein kinases (CDPKs) are a class of multifunctional serine/threonine (Ser/Thr) protein kinases involved inCa2+ signalling in plants andmediate the signalling cascade triggered bychanges in concentration of intracellular free calcium (Ca2+ ), to result in intracellular signalling and various physiological responses of plants to biotic as well as abiotic stress conditions, during plant growth and development, but primarily involved in plant innate immunity. CDPKs are group of calcium-binding proteins with kinase activity that are only found in plants and some protozoans. CDPKs form large gene family having multigenes with diversified roles, the structure, and functions of which are elucidated in many plants. The short review delineates major classes of calcium sensor proteins and discusses the structure and multitude functions of CDPKs in plants.